The domestication of Venezuela's Foreign Policy (2013-2017) - Barreto, Luis Maximiliano (2018)
The aim of this paper is to study the Foreign Policy of Venezuela from the beginning of Nicolás Maduro´s presidency to present day (2013-2017). Due to the limited time period under consideration and its proximity to the present, this article is guided by a preliminary hypothesis that holds that Venezuelan foreign policy underwent a process of "domestication", that is, an excessive absorption of the internal crisis by the external behavior of the State. By reviewing the main relations between Venezuela and its interlocutors, it becomes apparent that their actions are continuously permeated by domestic conflict. Primarily, this article reviews the guidelines for foreign policy in the government program and addresses the linkage between the main actors. In addition to assessing the validity of the preliminary hypothesis, this article reviews the foreign policy proposal in order to evaluate if the Venezuela´s external actions have remained in agreement with said proposal.